Morphology and ultrastructure of the digestive gland ofBithynia siamensis goniomphalus (Prosobranchia: Bithyniidae) and alterations induced by infection with the liver flukeOpisthorchis viverrini (Trematoda: Digenea) - Adam, Ralf; Pipitgool, V.; Sithithaworn, P.; Hinz, Erhard; Storch, Volker (Parasitology research, 1995)
The morphology and ultrastructure of the digestive gland ofBithynia siamensis goniomphalus and its alteration by infection withOpisthorchis viverrini were investigated by light and electron microscopy. The digestive gland ofB. s. goniomphalus was composed of three different cell types: digestive cells, excretory cells, and narrow cells. In infected animals the number of excretory cells increased dramatically. Cellular injury in digestive cells as well as in excretory cells following the infection could be observed at the ultrastructural level.
Gesehen am 30.10.2025